Comparative Analysis of Financial Regulation US-UK-EU - Anita PEŠA (Communications of International Proceedings, 2021)
The paper explores the level and direction of financial regulation in EU and gives insight in the steps of financial regulations through the paste decades. Financial markets and instruments are the most regulated industry due to explosion of the financial innovations in the last decades and due to increase of global financial integration. New financial instrument represents dynamic tool for increase whole economy in the time of expansion but also represent threat in the time of crises as we have fresh memories from the world crisis 2008. Financial regulation should be analysed from the global perspective, therefore author use comparative methodologies of financial regulation in EU, Great Britain and US to find the answer to the question regarding changes in global financial market. Main finding of the paper is the fact that, ironically, Covid-19 help financial integration in general and more specific, re-regulation in EU to became more dynamic, fluid (through EU financial instruments such as bonds) and applicable in each of EU member states.
Keywords: financial regulation; EU financial re-regulation; NextGeneration EU